Listening-with the subaltern: Anthropocene, Pluriverse and more-than-human agency - Carvalho, António (2022)
The Anthropocene brings to the fore the need to foster ontologies that reject the modern “one-world world” (Law 2015) model, characterized by extractivism, dualism and human exceptionalism, requiring the enactment of pluriverses (de la Cadena & Blaser 2018) that recognize the heterogeneous clamor of human and non-human agency. As an attempt to listen-with those oppressed and silenced by the modern extractivist paradigm, in this paper, we propose the mobilization of relational, dialogic and nondualistic methodologies that attend to subaltern and more-than-human worlds. Drawing on a variety of sources – such as the Parliament of Things, the Council of All Beings, the Pedagogy of the Oppressed, meditative and artistic practices –, our article speculatively engages with affective, situated, hybrid and counter hegemonic methodologies that articulate contemplative practices, the arts, more-than-human agency and local communities, recognizing that politics, aesthetics and affect are intimately entwined. Our experimental endeavour is centred on three case studies that encapsulate some of the socio-political and technological tensions of our current zeitgeist – wildfires, geoengineering, and lithium mining –, speculating on how pluriversal methodologies can bring to the fore the many worlds silenced by the modern “one-world world”.